Consumo de esteroides anabólicos androgénicos y déficit de las funciones ejecutivas en fisicoculturistas de la ciudad de Loja - Jiménez Abad, Marlon Eduardo (2021)
In previous studies, synthetic derivatives of testosterone, called anabolic androgenic steroids, have been linked to functional and structural toxic effects at the brain level involved with cognitive sub-processes dedicated to achieving a goal or solving problems, which are called executive functions. The purpose of this study was to relate the consumption of anabolic androgenic steroids, and the time of their consumption, with the presence of deficits in executive functions, in bodybuilders from the city of Loja. The study is descriptive, analytical, cross-sectional and prospective. The sample consisted of 23 male bodybuilders between the ages of 20 and 59, organized into two groups: consumers (n=11) or not (n=12) of anabolic androgenic steroids. Four neuropsychological tests were applied to assess executive functions and we found that users of anabolic androgenic steroids and those who had consumed them for a longer time had poorer performance in test scores, with a significant difference (p < 0.05), with respect to the scores obtained. by non-users and those who had used these substances for less time. Demonstrating that the variables consumption of anabolic androgenic steroids and time of consumption had an influence on the scores of the tests that evaluated executive functions. We conclude, in this way, that the consumption of anabolic androgenic steroids, and the time of their consumption, is related to the presence of deficits in executive functions. Keywords: executive functions, bodybuilders, anabolic androgenic steroids.